Peran Hukum Kontrak Digital dalam Pengelolaan Risiko Bisnis E-Commerce di Era Digital - Dena Vera Silvana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate the effectiveness of digital contract law in mitigating e-commerce business risks in Indonesia’s digital economy, focusing on three local platforms (XYZ, ABC, DEF) from January to November 2024. Using a qualitative case study approach, data were collected through semi-structured interviews with 15 business actors (UMKM owners, platform managers, and legal practitioners) and analysis of regulatory documents (Electronic Information and Transaction Law, PDP Law). Thematic analysis via NVivo 12 revealed that 70% of platforms lack explicit personal data protection clauses, while 85% of MSMEs use generic contract templates, increasing legal disputes by 40%. Cybersecurity challenges were exacerbated by low budget allocation (5% of revenue), leading to vulnerabilities in 3 out of 10 MSMEs. The study recommends: (1) AI-based regulatory education platforms for MSMEs, (2) standardized digital contract guidelines with mandatory cyber-risk clauses, and (3) fiscal incentives for cybersecurity investment. These findings contribute to legal theory by bridging the gap between normative frameworks and practical risk management, while offering actionable strategies for policymakers and businesses to enhance transactional security and compliance..